Morpho-Functional Aspects of Atopic Dermatitis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Atopic dermatitis(AD) is a skin disease characterized by severe itching, chronic recurrent course, predominance of urticary and papular elements in the clinical picture in combination with signs of atopy. Atopy is understood as a hereditary predisposition to allergic reactions in response to sensitization by certain antigens.